1998
DOI: 10.1038/sj.jhh.1000620
|View full text |Cite
|
Sign up to set email alerts
|

Differences between amlodipine and lisinopril in control of clinic and twenty-four hour ambulatory blood pressures

Abstract: The anti-hypertensive efficacy of once-daily amlodipine (up to 10 mg) and lisinopril (up to 20 mg) were compared in terms of clinic and ambulatory blood pressure (BP) control, in an observer-blind, two-period crossover study. Following a 4-week placebo run-in period, patients underwent two active treatment phases each lasting 12 weeks and separated by a 4-week washout period. Sixty patients with a supine diastolic BP between 90 and 120 mm Hg were included, irrespective of whether or not they had received previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 11 publications
(10 reference statements)
0
6
0
Order By: Relevance
“…Among the dihydropyridine derivatives, amlodipine has a distinct pharmacokinetic profile with a long half life of 34 h; thus, single daily dosing enables steady-state plasma concentrations to be achieved (18). Clinical studies based on ambulatory blood pressure monitoring (ABPM) have confirmed that amlodipine is more effective in controlling morning blood pressure after awakening than other CCBs with short plasma half lives (19) or angiotensin converting enzyme inhibitors (20). However, we have previously observed that 19% of patients under longterm amlodipine monotherapy experience morning hypertension with an average morning systolic blood pressure (SBP) over 135 mmHg, despite the fact that their average evening SBPs are adequately controlled at below 135 mmHg (21).…”
Section: Introductionmentioning
confidence: 94%
“…Among the dihydropyridine derivatives, amlodipine has a distinct pharmacokinetic profile with a long half life of 34 h; thus, single daily dosing enables steady-state plasma concentrations to be achieved (18). Clinical studies based on ambulatory blood pressure monitoring (ABPM) have confirmed that amlodipine is more effective in controlling morning blood pressure after awakening than other CCBs with short plasma half lives (19) or angiotensin converting enzyme inhibitors (20). However, we have previously observed that 19% of patients under longterm amlodipine monotherapy experience morning hypertension with an average morning systolic blood pressure (SBP) over 135 mmHg, despite the fact that their average evening SBPs are adequately controlled at below 135 mmHg (21).…”
Section: Introductionmentioning
confidence: 94%
“…7,14 In our study, amlodipine once daily in the morning reduced the BP level throughout the day and night in both dippers and non-dippers. In nondippers, night time and morning high BP were well reduced by amlodipine.…”
Section: Journal Of Human Hypertensionmentioning
confidence: 90%
“…The same phenomenon was observed in a report comparing amlodipine and lisinopril. 7 We suggest three possible explanations for this phenomenon. First, the plasma half-life of temocapril (14.5-21.5 h) is shorter than that of amlodipine (35-48 h).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Irbesartan proved more effective than losartan in two separate studies that used seated diastolic blood pressure as a primary efficacy endpoint [20,21]. Amlodipine reduced both supine systolic and diastolic blood pressure more than lisinopril [22].…”
Section: Challenges In Evaluating the Costeffectiveness Of Antihypertmentioning
confidence: 99%